Association of Multidrug-Resistant Tuberculosis (MDR-TB) Patients on Profile of Liver and Kidney Function - Muda, Iskandar; Adam, Muhammad Fadlan; Saputra, Rudi; Muhyi, Annisa; Noprianto, Dwi; Aminuddin, Muhammmad (Jurnal Kesehatan Pasak Bumi Kalimantan, 2022)
Introduction: Therapy of multidrug-resistant tuberculosis (MDR-TB) patients is still not handled properly, is more toxic, and is more high-priced. The liver is the primary metabolism, and the kidney is the main excretion organ. The study aims to know the association of multidrug-resistant tuberculosis (MDR-TB) patients on profile of liver and kidney function Methods: The research is a cross-sectional study with consecutive sampling. Twenty-four respondents were confirmed as MDR-TB patients without HIV who had done biochemical tests. Results: We found that sex of MDR-TB patients on liver function; ALT (p = 0.124) and AST (p = 0.077) and kidney function; BUN (p = 0.270), creatinine (p = 0.137).  Age of MDR-TB patients on liver function; ALT (p = 0.587) and AST (p = 0.093) and kidney function; BUN (p = 0.423), creatinine (p = 0.142). Comorbid on MDR-TB patients on liver function; ALT (p = 0.756) and AST (p = 0.244) and kidney function; BUN (p = 0.816), creatinine (p = 0.612). Conclusions: There were no association in sex, age, and comorbid of MDR-TB on liver and kidney function.